(untitled) (International Journal of Ayurveda and Pharma Research, 2015)
The demand for herbal products as food supplements, food additive and traditional medicine for health care is increasing globally. There are several reports of adverse effects of these herbal preparations due to the presence of high level of heavy metals such as Lead, Cadmium, Arsenic, Mercury, Chromium, Nickel, Copper etc and this problem has become a matter of concern. The present study was done to determine the presence of Arsenic in some of the selected medicinal plants namely Hemidesmus indicus (L.) R.Br. (Sariba), Cyperus rotundus L. (Musta), Glycyrrhiza glabra L. (Yashtimadhu), Rubia cordifolia L. (Manjishta), Eclipta alba Hassk (Bhringaraj), Hedychium spicatum Ham.ex Smith (Karchura), Emblica officinalis Gaertn. (Amalaki) and Acacia concinna (Willd.) DC. (Shikakai), which were procured from local market of Chennai, Tirupati and Hyderabad. The samples were digested by wet digestion method and analysed by UV-Vis Spectrophotometer. The results were compared with permissible limits recommended by WHO. Mean levels were evaluated with respect to their procurement. It was observed that the analyzed plant species contained safe levels of the heavy metals concentration excepting a very few samples. There was a considerable variation of heavy metal concentration for the examined medicinal plant species. This is due to the difference in physiological properties of plant uptake.